ARTIFICIAL INTELLIGENCE, ARMED CONFLICT, CATHOLIC THEOLOGICAL ETHICS - O'Brien, Roderick (Asian Horizons, 2020)
Artificial intelligence provides the complex software for autonomous weapons, a new contribution to the arsenals available for contemporary and future armed conflict. This paper first provides an overview of Catholic Theological Ethics, including the Just War Doctrine, Christian Pacifism, and the priority for peace. In the second part, the paper provides a brief introduction to autonomous weapons, using two examples. In this part, autonomous weapons are linked to the Just War Doctrine, and to the question of responsibility. The third part of the paper brings these two topics together. The third part includes an insight into the ways the Just War Doctrine is challenged by autonomous weapons and the need for respectful dialogue between ethicists and developers of weapons, and the priority of peace. No final conclusion is possible: this is a field of constant change and interchange. But during this work in progress, we can be attentive to the challenges to Catholic Theological Ethics, and to the contributions of Catholic ethicists and Vatican officials.